Autocatalytic Delivery of Brain Tumor–Targeting, Size‐Shrinkable Nanoparticles for Treatment of Breast Cancer Brain Metastases. (20th February 2020) - Zhang, Shenqi; Deng, Gang; Liu, Fuyao; Peng, Bin; Bao, Youmei; Du, Fengyi; Chen, Ann T.; Liu, Jun; Chen, Zeming; Ma, Junning; Tang, Xiangjun; Chen, Qianxue; et al.
Abstract: Breast cancer brain metastases (BCBMs) represent a major cause of morbidity and mortality among patients with breast cancer. Chemotherapy, which is widely used to treat tumors outside of the brain, is often ineffective on BCBMs due to its inability to efficiently cross the blood‐brain barrier (BBB). Although the BBB is partially disrupted in tumor lesions, it remains intact enough to prevent most therapeutics from entering the brain. Here, a nanotechnology approach is reported that can overcome the BBB through synthesis of lexiscan‐loaded, AMD3100‐conjugated, shrinkable nanoparticles (NPs), or LANPs. LANPs respond to neutrophil elastase–enriched tumor microenvironment by shrinking in size and disrupt the BBB in tumors through lexiscan‐mediated modulation. LANPs recognize tumor cells through the interaction between AMD3100 and CXCR4, which are expressed in metastatic tumor cells. The integration of tumor responsiveness, tumor targeting, and BBB penetration that enables LANPs to penetrate metastatic lesions in the brain with high efficiency is demonstrated and, when doxorubicin is encapsulated, LANPs effectively inhibit tumor growth and prolong the survival of tumor‐bearing mice. Due to their high efficiency in penetrating the BBB for BCBMs treatment, LANPs have the potential to be translated into clinical applications for improved treatment of patients with BCBMs. Abstract : A nanotechnology approach is developed and validated for targeted drug delivery to breast cancer brain metastases (BCBMs) through the synthesis of lexiscan‐loaded, AMD3100‐conjugated, shrinkable nanoparticles (LANPs). LANPs have the potential to serve as a versatile platform for the delivery of therapeutic agents to improve treatment of BCBMs.